Answer:
Explanation:
You balance the equation by getting rid of the variable on one side and then you get rid of the constant on the other then solve from there
10-5=-6+2p
10p-5-2p=-6+2p-2p
8p-5+5-6+5
8p=-1
p=
To solve the equation we put -1/8 in the p spot:
10x-1/8-5=-6+2x-1/8
-1.25-5=-6+-0.25
-6.25=-6.25
The equation = -6.25
Arrange similar algebra given there ... which is 'p' here , Now ;
10p -5= - 6+2p
or, 10p -2p = -6+5
( NOTE : Moving to opposite side , + becomes - and - becomes + )
10p -2p = -6+5
8p = - 1
p = - 1 / 8
5.7m questions
7.4m answers